The Ability of Trichoderma sp and Pseoudomonas fluorencens to Inhibit the Growth of Anthracnose Fungus In Vitro at BBPP Ketindan Lawang - Dykha Maretha Setyawan; Endang Triwahyu Prasetyawati (Future Science, 2023)
Anthracnose is an important disease in chili plants because yield losses can reach 80%. This disease is caused by the fungus Colletotricum spp. The control that is often used is with chemical pesticides which cause negative effects on the environment. The refore it is necessary to use alternative control using biological agents that are environmentally friendly and support sustainable agriculture. This activity aims to determine directly the causes of anthracnose disease and the inhibition percentage of Tricoderma sp and Pseoudomonas fluorencens against anthracnose fungi in vitro on chili plants at the Ketindan Agricultural Training Center (BBPP). The test used the pour plate method (combining media with biological agents) with 3 treatments, 3 replications and 1 control. The test results showed that Trichoderma sp had an inhibition percentage of 100% while Pseudomonas fluorencens had an inhibition percentage of 28.06% and 100%. Trichoderma sp can inhibit the growth of anthracnose fungi because it has a competition mechanism for nutrients and space, hyper-parasitism, and produces antibiotic compounds while Pseoudomonas fluorencens has a mechanism for producing antibiotic compounds. Based on the observations, it can be concluded that Trichoderma sp and Pseoudomonas fluorencens were able to inhibit the growth of the fungus Colletotricum gloeospoioides in vitro.